Finding a mission in bureaucracies: How authentic leadership and red tape interact - Rick Vogel; Dominik Vogel; Artur Reuber (Public Administration, 2022)
Finding a mission is important for employees to perform well in public service jobs. Research has demonstrated that leadership can facilitate mission valence among followers, but if and how leadership unfolds this effect in the presence of excessive bureaucracy (i.e., red tape) is unclear. This interaction is particularly interesting in the case of authentic leadership (i.e., a positive leadership style based on self-awareness, consistent behaviors, and transparent relations with followers), as red tape may either neutralize or enhance the association of authentic leadership with mission valence. We test these rivalry hypotheses in a sample from a two-wave survey among public employees in Germany. Results provide support for the neutralization hypothesis, as the relationship between authentic leadership and mission valence strengthens at lower levels of red tape. HR practitioners are thus challenged to reduce red tape and to make public organizations authentic places, where leaders can develop authenticity through self-awareness.
Keywords: 340